Akysis poecilurus, a new species of catfish from southern Myanmar (Actinopterygii: Siluriformes: Akysidae) - Ng, Heok Hee; Kottelat, Maurice (Zootaxa, 2026)
Akysis poecilurus, a new species of catfish, is described from the Lenya River drainage in southern Myanmar. It is distinguished from congeners in Myanmar by the color pattern of the body and caudal fin, as well as morphometry. Akysis poecilurus differs from congeners outside of Myanmar by pectoral-spine morphology and the color pattern of the body. This represents the eighth species of Akysis recorded from Myanmar.